1994
DOI: 10.1152/ajpcell.1994.266.2.c376
|View full text |Cite
|
Sign up to set email alerts
|

Soluble alpha v beta 3-integrin ligands raise [Ca2+]i in rat osteoclasts and mouse-derived osteoclast-like cells

Abstract: We evaluated the possible involvement of intracellular Ca2+ concentration ([Ca2+]i) changes in the action of alpha v beta 3-ligands, known to regulate osteoclast function. Rat osteoclasts or mouse osteoclast-like cells, as examined by microfluorimetry and fura 2, showed a transient [Ca2+]i increase when perfused with (all 0.1 microM) vitronectin, osteopontin, polypeptide echistatin, fibronectin, and Arg-Gly-Asp-Asp and Arg-Gly-Asp-Ser peptides (10(-4) M) but not with laminin, collagen I, collagen IV, or [Ala24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 22 publications
2
44
0
Order By: Relevance
“…It is also produced by the cells in nonskeletal tissues and has been implicated in tumorigenesis (17,18). Substrate-bound OPN promotes attachment of osteoclasts (19,20), whereas soluble OPN can alter calcium levels in osteoclasts (21,22), suppress inducible nitric-oxide synthase induction in kidney cells, and macrophages and serve as a chemoattractant (17,18,23). These observations suggest that OPN may play a key role both in cell attachment and in controlling subsequent bone cell functions such as resorption.…”
Section: Introductionmentioning
confidence: 99%
“…It is also produced by the cells in nonskeletal tissues and has been implicated in tumorigenesis (17,18). Substrate-bound OPN promotes attachment of osteoclasts (19,20), whereas soluble OPN can alter calcium levels in osteoclasts (21,22), suppress inducible nitric-oxide synthase induction in kidney cells, and macrophages and serve as a chemoattractant (17,18,23). These observations suggest that OPN may play a key role both in cell attachment and in controlling subsequent bone cell functions such as resorption.…”
Section: Introductionmentioning
confidence: 99%
“…55 The present cDNA array studies revealed increased ACE expression in the desmin-null hearts, which might contribute to osteopontin induction through angiotensin II. In turn, osteopontin could modulate calcium levels by different ways including calcium mobilization, 56,57 activation of Ca ϩϩ ATPase pump, 58 Ca ϩϩ binding, 59 and by modulating hydroxyapatite crystal growth. 38 Thus, abnormalities in mitochondria apart from cytochrome c-and caspase-related prodeath events, can initiate and maintain the Ca ϩϩ /osteopontin cycle described above, which could lead to the extensive calcification in desmin-null hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, signal transduction mediated by the β3 cytoplasmic tail is critical for integrin function in the osteoclast. Previous studies have demonstrated that binding of RGD-containing peptides to the integrin triggers various intracellular signals, including changes in intracellular calcium (24)(25)(26), and activation of c-src (8), PYK2 (9), p130cas (27), and PI3-kinase (28). Despite these observations, the structural components of the β3 cytoplasmic tail mediating osteoclast function have not been elucidated.…”
Section: Figurementioning
confidence: 99%